2018
DOI: 10.1109/tmi.2018.2851150
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Global Glomerulosclerosis in Transplant Kidney Frozen Sections

Abstract: Transplantable kidneys are in very limited supply. Accurate viability assessment prior to transplantation could minimize organ discard. Rapid and accurate evaluation of intra-operative donor kidney biopsies is essential for determining which kidneys are eligible for transplantation. The criterion for accepting or rejecting donor kidneys relies heavily on pathologist determination of the percent of glomeruli (determined from a frozen section) that are normal and sclerotic. This percentage is a critical measurem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(124 citation statements)
references
References 44 publications
1
107
1
3
Order By: Relevance
“…Whole slide images (WSI) were scanned at 20x magnification from hematoxylin & eosin (H&E) stained slides. The slides from the Pakistan cohort were scanned at Aga Khan [43,44], and has also been adapted for research purposes.…”
Section: Digital Pathology Workflowmentioning
confidence: 99%
“…Whole slide images (WSI) were scanned at 20x magnification from hematoxylin & eosin (H&E) stained slides. The slides from the Pakistan cohort were scanned at Aga Khan [43,44], and has also been adapted for research purposes.…”
Section: Digital Pathology Workflowmentioning
confidence: 99%
“…The object detection confusion matrices for SegNet and DeepLab v3+ are reported in Tables 10 and 11, respectively. The detection metrics for both the proposed models and a comparison with the method proposed by Marsh et al [8] are reported in Table 12. The SegNet-based model obtained a better F-score for both the glomeruli classes.…”
Section: Object Detection Metricsmentioning
confidence: 99%
“…In the realm of digital pathology, several recent studies have proposed CAD systems for glomerulus identification and classification in renal biopsies [1][2][3][4][5][6][7][8]. The eligibility for transplantation of a kidney retrieved from Expanded Criteria Donors (ECD) relies on rush histological examination of the organ to evaluate suitability for transplant [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations